2016
DOI: 10.1371/journal.pone.0153311
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes Associated with Litter Size in Berkshire Pig Placenta

Abstract: Improvement in litter size has become of great interest in the pig industry because fecundity is directly related to sow reproductive life. Improved reproduction has thus been achieved by elucidating the molecular functions of genes associated with fecundity. In the present study, we identified differentially expressed genes (DEGs) via transcriptomic analysis using RNA-sequencing (RNA-Seq) in Berkshire pig placentas from larger (LLG, mean litter size >12) and smaller (SLG, mean litter size < 6.5) litter size g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…The final libraries were quantified using a KAPA Library Quantification kit (KAPA Biosystems, South Africa) and an Agilent 2100 Bioanalyzer. After qRT-PCR validation, the libraries were subjected to paired-end sequencing with a pair-end 150-base pair reading length on an Illumina HiSeq sequencer (Illumina) [30].…”
Section: Rna Sequencingmentioning
confidence: 99%
“…The final libraries were quantified using a KAPA Library Quantification kit (KAPA Biosystems, South Africa) and an Agilent 2100 Bioanalyzer. After qRT-PCR validation, the libraries were subjected to paired-end sequencing with a pair-end 150-base pair reading length on an Illumina HiSeq sequencer (Illumina) [30].…”
Section: Rna Sequencingmentioning
confidence: 99%
“…Increasing litter size and raising healthy, quality animals are crucial factors in the livestock industry [1].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the genetic traits controlling the reproductive physiology has become an important research topic in the last decade [1]. Litter size is a complex trait in multiparous mammals.…”
Section: Introductionmentioning
confidence: 99%
“…To find the quantitative trait loci (QTL) and causal genes for these traits, several studies for linkages [11-13] and candidate genes ([14-17] have been conducted by using modern molecular information. Many of the major genes involved in the prolificacy of pig, such as ESR , FSHB , RBP4 , PRLR , MTNR1A , OPN , BMP families, and GDF9 genes have been characterized [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have revealed an increasing number of associated QTLs and candidate genes involved in pig litter size [20-22]. Recently, several studies of the transcriptome for reproductive organs reveals differentially expressed genes affecting reproduction and candidate genes for litter size in European pig breeds [9, 15, 17] and Chinese indigenous pig breeds [14, 23]. Although QTLs and candidate genes have been reported to affect the litter size in many pig breeds, however, the studies were only focused on specific species or breeds and the findings cannot elucidate the marked differences of the reproductive traits between Asian and European pig breeds and the variations of litter size between pigs.…”
Section: Introductionmentioning
confidence: 99%